Ius Constituendum of Regulating Trading in Influence as a Form of Corruption Offense in Indonesia - I Wayan Satria Pratama Bayu Negara; Annisa Virgi Azzahra (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2026)
Corruption offense is an extraordinary crime that requires special handling. The modus operandi of corruption offenses always vary, and even several other forms of corruption offenses have been regulated under UNCAC, one of which is Trading in Influence. Nevertheless, Indonesia has not yet adopted Trading in Influence as a corruption offense in its positive law. This study is a legal research type that uses statutory, conceptual, and comparative approaches. The legal sources employed include primary, secondary, and tertiary legal materials, which were inventoried and then analyzed using a descriptive-analytical method. The study aims to determine the urgency of regulating trading in influence in Indonesia and to compare the regulation of trading in influence among Indonesia, France, and Spain. The results show that, in its characteristics, trading in Influence meets the elements of a corruption offense because it involves the use of influence by an individual or a corporation toward a state administrator to obtain a benefit. The absence of explicit rules on trading in influence in the Indonesian Law on the Prevention of Corruption (UU PTPK) creates a legal gap that is exploited by corrupt actors. Indonesia has not adopted trading in influence in its positive law. Unlike countries such as France and Spain, which have clearly regulated this offense in their Penal Codes by distinguishing between active and passive actors, Indonesia needs to promptly regulate the trade of influence (Trading in Influence) as a corruption offense to close the legal gap and strengthen anti-corruption efforts.